2014
DOI: 10.1346/ccmn.2014.0620204
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Diagenesis and Thermal Maturation of the Cretaceous Marias River Shale, Disturbed Belt, Montana

Abstract: The hypothesis that chemical remanent magnetization (CRM) in argillaceous rocks may be due to release of Fe during smectite illitization has been tested by study of spatial and temporal relationships of CRM acquisition, smectite illitization, and organic-matter maturation to deformation in the Montana Disturbed Belt. New K-Ar ages and stacking order and percentages of illite layers in illite-smectite (I-S) are consistent with conclusions from previous studies that smectite illitization of bentonites in Subbelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…They clearly prove that a predominant fraction of 40 Ar remains in its initial interlayer position and that the recoil-induced 40 Ar l oss is negligible. This is experimentally supported by numerous K-Ar dating studies on the finest illite-smectite subfractions showing no considerable Ar loss (Clauer et al, 1997;Środoń et al, 2002;Osborn et al, 2014) and by 40 Ar/ 39 Ar illite dating model of the 39 Ar recoil random walk (Hall et al, 2000), which has been remarkably successful in explaining stereotypical age spectral shapes.…”
Section: Conclusion and Implications For Ar-based Geochronologymentioning
confidence: 54%
See 1 more Smart Citation
“…They clearly prove that a predominant fraction of 40 Ar remains in its initial interlayer position and that the recoil-induced 40 Ar l oss is negligible. This is experimentally supported by numerous K-Ar dating studies on the finest illite-smectite subfractions showing no considerable Ar loss (Clauer et al, 1997;Środoń et al, 2002;Osborn et al, 2014) and by 40 Ar/ 39 Ar illite dating model of the 39 Ar recoil random walk (Hall et al, 2000), which has been remarkably successful in explaining stereotypical age spectral shapes.…”
Section: Conclusion and Implications For Ar-based Geochronologymentioning
confidence: 54%
“…In the case of K-Ar age variability among finest subfractions that should represent purely authigenic clay (i.e. < 0.2 µm in bentonites), their crystallization history and illite-smectite crystallite growth may play a major role (Clauer et al, 1997;Środoń et al, 2002;Osborn et al, 2014). On the other hand, Lerman and Clauer 5 (2005) and Lerman et al (2007) have suggested post-crystallization diffusion in the diagenetic zone as a mechanism responsible for lower K-Ar isotope age estimates of finer particles, as compared to coarser ones.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if there were detrital contaminants they have been shown to diminish in abundance in the progressively smaller size fractions of clay (Pevear, 1999). The bentonite, while fairly impermeable relative to sandstones, is infiltrated by porefluids from the surrounding shale, allowing alteration of the volcanic glass (ash) to smectite first, then illite with increasing temperature and K supply (Altaner et al, 1984;Elliott et al, 1987;Altaner, 1989;Williams and Ferrell, 1991;Clauer et al, 2014a;Osborn et al, 2014). Crystallization of illite in bentonites occurs at 60˚-150˚C; temperatures of hydrocarbon generation (Tissot and Welte, 1984;Hower et al, 1976) when B and Li are released from source rocks (Williams et al, 2001;.…”
Section: Illite Crystal Growth In Wattenberg Bentonitesmentioning
confidence: 99%
“…Ar/ 39 Ar illite dating is commonly used to analyze the timing of various geological processes in the upper crust, including diagenesis and hydrocarbon formation (Pevear, 1999;Dong et al, 2000;Clauer et al, 2011;, low grade metamorphism (Dong et al, 1997;Merriman and Peacor, 1999;Verdel et al, 2011), epithermal ore formation (Hall et al, 1997 and, faulting (e.g., van der Pluijm et al, 2001;Solum and van der Pluijm, 2005;Haines and van der Pluijm, 2008;Osborn et al, 2014), and folding (Fitz-Díaz and van der Pluijm, 2013;Fitz-Díaz et al, 2014a). Illite is one of the few K-bearing minerals that form under diagenetic and anchizonal conditions ( Fig.…”
Section: Introductionmentioning
confidence: 99%